Topographic Relief Response to Fluvial Incision in the Central Tibetan Plateau: Evidence From Cosmogenic 10Be. Issue 10 (22nd October 2021) - Yang, Ye; Cui, Li‐Feng; Xu, Sheng; Liu, Cong‐Qiang; Fabel, Derek
Abstract: Fluvial incision, regarded as one of the fundamental geomorphic processes, drives the evolution of mountainous landscapes. The transitional landscape from low‐relief to high‐relief in the central Tibetan Plateau is rapidly evolving as it is influenced by river dynamics, climate change and tectonic uplift. Combining cosmogenic 10 Be depth profile dating and topographic analysis, this study provides new constraints on the formation and destruction of low‐relief surfaces in the central Tibetan Plateau. We find that the high‐relief landscape in the Suoqu area (a major tributary of the upper Nu River) shows a rapid fluvial incision rate of 710 ± 70 mm kyr −1 since the late Pleistocene, while the low‐relief topography in the adjacent Xiaqiuqu area presents an order of magnitude lower incision rate of 70 ± 10 mm kyr −1 . These results are consistent with the long‐term (multi‐million‐year) exhumation rates derived from low‐temperature thermochronology, suggesting that this region has experienced an evolving incision history. We interpret that the higher relief was caused by enhanced fluvial incision, and the lower relief was slowly developed by sedimentation and relatively steady low exhumation rate. The presence of a knickzone appears to mark the boundary between these differentially incising landscapes, which may be caused by rapid headward retreat and higher river discharge in the Suoqu River. The coincidence of fluvial terraces ages with climate‐driven events, in addition to paleodenudation rates, indicates that the formation of fluvial terraces in the Xiaqiuqu and Suoqu areas might be associated with the quick sedimentation of weathered materials in early warming periods. Plain Language Summary: Understanding the formation mechanisms of topographic relief is crucial for interpreting the contrast between the low‐relief surfaces in the central Tibetan Plateau and the high‐relief plateau margin. In this study, fluvial terraces, which directly record landscape incision history, are used to interpret the relationship between fluvial incision and topographic relief in two tributaries of the upper Nu River. We present new terrace formation ages derived from cosmogenic 10 Be, a rare radioisotope produced in quartz. We find that the formation ages of terraces since the late Pleistocene are coincident with regional climate change events. Fluvial incision rate in the relatively low‐relief Xiaqiuqu area calculated by dividing the terrace height above the modern river by the exposure age is 70 ± 10 mm kyr −1, which is an order of magnitude lower than that in the high‐relief Suoqu area (710 ± 70 mm kyr −1 ). Together with river profile analysis in the Xiaqiuqu and Suoqu areas, we interpret that relief is probably controlled by the sharp change in channel slope, which, in turn, is influenced by tectonically driven rapid headward retreat and climate‐driven river discharge. Key Points: Steady state topographic relief has been reached in the Xiaqiuqu area, but not in the adjacent Suoqu area The formation of fluvial terraces in the study areas is associated with the quick sedimentation of materials in early warming periods Fluvial incision rate of the high relief landscape is an order of magnitude higher than low relief landscape in the upper Nu River region